Pendampingan pada Petani Mawar Tabur di Desa Tapak Kecamatan Panekan Kabupaten Magetan - Andayanie, Wuye Ria (JURNAL DAYA-MAS, 2018)
Rose (Rosa hybrida L.) is classified as the genus Rosa and is an ornamental flower plant in the form of herbs with thorny stems. Roses have many types, one of which is a type of sowing roses that are widely grown in Tapak Village, Panekan Subdistrict. Sowing roses can be used as a support for daily economic needs by residents in Tapak Village. In addition, rose plants can be used as conservation plants, if planted on a bench terrace on sloping land. The Panekan area is an area declared by the Magetan Regency Government as an area prone to landslides. Until now the terraces of sloping land in Tapak Village are often not utilized with terrace reinforcing plants, so land degradation is increasing and expanding, mainly due to the high level of soil erosion, especially in sloping areas. Utilization of conservation techniques with rose plants on sloping lands prone to erosion can reduce degradation of soil fertility. Therefore it is necessary to provide assistance for: 1) planting a terrace with rose plants; 2) supply of rose seeds and non-dependence on synthetic chemical fertilizers. Community service activities are held from October to December 2018. Each partner farmer is given training and is facilitated to supply sowing roses and compost plus for nurseries. The method of activity uses a group approach, field meeting, farmer course. The mentoring activity was carried out with a pattern of rural appraisal Participatory, namely working with members of farmer groups in Tapak Village. The results of the mentoring activities were carried out to increase the income of sowing rose farmers and reduce degradation on sloping land.Â Keywordsâ€”: sowing roses, terrace, degradation, Tapak VillageÂ